Draft (Revised) Second Five Year Plan 1956-1961 Government of Saurashtra - Planning Commission (Planning Commission, 1955)
The proposals of the Second Five Year Plan of Saurashtra are the result of the Integration and rationalisation of the development programmes contained in the village and district plans and the proposals of the various Government Departments modified in light of discussions with the Planning Commission and in the Working Groups set up by the Planning Commission.
Directorate of Statistics and Planning Government of Saurashtra
Directorate of Statistics and Planning Government of Saurashtra